Comparative and socio-critical approach to the novels Navel of the World by Venko Andonovski and Dobri dani by Marko Denić in German language studies - Marina M. Petrović Jilih (University of Belgrade, Teacher Education Faculty, 2023)
Building on the current scientific and literary-didactic discourse, this paper has as its subject the analysis of the group discussion and the categorization of the so-called functional literary competences which students of German language studies should master. The focus of dealing with literary texts in the eighth semester of the German language studies is, apart from their literary nature, primarily their socio-political impulses and influence on the transfer from the world of the text to the world around us. By comparing the two novels, The Navel of the World by Venko Andonovski and Dobri dani by Marko Dinić, and by means of their productive treatment in the classroom, we will see whether literary texts contribute to the development of the social-critical engagement of the recipients. Along with observing and defining the didactics of literature as an applied science and a part of the literary social system, qualitative scientific methodology was applied in this research. After the semi-structured group discussion procedure, the obtained data were analyzed and categorized. The research questions supported by theoretical postulates important for this paper arose from teaching practice, while methodological examples and research results bring it back to that practice.